Assessment of low cycle fatigue improvement of machined AISI 316 stainless steel by brush hammering. (24th March 2014) - Sidhom, N.; Makhlouf, K.; Khlifi, A.; Braham, C.; Sidhom, H.
ABSTRACT The effects of wire brush hammering on low cycle fatigue behaviour of AISI 316 austenitic stainless steel has been investigated on turned samples through an experimental study combining strain controlled fatigue tests, scanning electron microscope examination and X‐ray diffraction analysis. An increase in fatigue life by 266% was reported at an imposed strain amplitude of Δεt/2 = 0.2%. This improvement is limited to Δεt/2 ≤ 0.5%. It is found that wire brush hammering produces a surface texture that favours, under cyclic loading, nucleation of randomly dispersed short cracks of the order of 50 µm in length stabilized by a compressive residual stress field. In contrast, turned surface showed much longer unstable cracks of the order of 200 µm in length nucleated in the machining groves and propagated under the effect of a tensile residual stress field. It has also been established that wire brush hammering can be used as intermittent treatment to improve the residual fatigue life of components subjected to cyclic loading. The treatment is very efficient if it is performed at a fraction of service lifetime ni/Nr lower than 0.5.